2018
DOI: 10.1371/journal.pone.0194606
|View full text |Cite
|
Sign up to set email alerts
|

Association between vasectomy and risk of testicular cancer: A systematic review and meta-analysis

Abstract: ObjectivesA number of researchers have reported that vasectomy is a risk factor for testicular cancer. However, this conclusion is inconsistent with a number of other published articles. Hence, we conducted this meta-analysis to assess whether vasectomy increases the risk of testicular cancer.Materials and methodsWe identified all related studies by searching the PubMed, Embase, and Cochrane Library database from January 01, 1980 to June 01, 2017. The Newcastle-Ottawa Scale (NOS) checklist was used to assess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The quality of observational studies was determined using the Newcastle-Ottawa Scale. Any study that scored over seven stars was regarded as a high-quality study, while a score of four to six stars was regarded as a moderate-quality study ( 33 ). A quality assessment of the RCTs was carried out using the Cochrane risk of bias tool ( Figures 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The quality of observational studies was determined using the Newcastle-Ottawa Scale. Any study that scored over seven stars was regarded as a high-quality study, while a score of four to six stars was regarded as a moderate-quality study ( 33 ). A quality assessment of the RCTs was carried out using the Cochrane risk of bias tool ( Figures 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two investigators (YL and DDL) extracted data independently using a predesigned data extraction form. The Newcastle-Ottawa quality assessment scale (NOS) was applied to evaluate the quality of the included observational studies [ 23 ]. The checklist contains three quality parameters: selected population, comparability of groups, and evaluation of exposures (for case-control) or outcomes (for cohorts) of interest [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each study was scored on a scale of 0 to 9. Studies with scores greater than or equal to 7 are generally considered to be of high quality [ 23 ]. The quality of each MR study was assessed independently by two investigators (YL and DDL) based on accepted criteria as previously reported [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two investigators (DL and YL) extracted data independently using a predesigned data extraction form. The quality of individual studies was assessed by the Newcastle-Ottawa Scale (NOS) for observational studies ( 27 ).…”
Section: Methodsmentioning
confidence: 99%